The Works of Peter Schott, 1460-1490, Vol. II Commentary - Cowie, Marian L.; Cowie, Murray A. (UNC Studies in the Germanic Languages and Literatures, 1971)
This companion volume to "The Works of Peter Schott, Vol. I: Introduction and Text" is an essential tool for gaining access to the writings of the humanist Peter Schott. The commentary volume comprises explanatory notes to Vol. I, including English summaries of all items and, in addition, pertinent cultural, economic, and political information. The editors have also included brief biographies of those persons mentioned in Schott's writings and their commentary, as well as fourteen appendices related to the text.